Fondasi Pemahaman Persepsi Teori Gestalt Dalam Persepsi Ilmu Psikologi - Anak Agung Ngurah Balawan Mahotama Prameswara; Adinda Nasha Ayu Febrianthi (Universitas Pendidikan Nasional, 2025)
Gestalt theory, developed by Max Wertheimer, Wolfgang Köhler, and Kurt Koffka in the early 20th century, emerged as a response to reductionist approaches such as behaviorism and structuralism. This theory emphasizes that the whole is more than the sum of its parts, and that human experience must be understood holistically. Wertheimer observed the phi phenomenon—an illusion of movement from a sequence of static images—to demonstrate that the brain naturally organizes visual information. Köhler, through studies on chimpanzees, asserted that problem-solving involves holistic insight. Koffka expanded the theory by introducing principles such as proximity, similarity, continuity, and closure. Gestalt theory highlights that the human brain actively seeks order amid complexity. Its contributions extend to perception, learning, memory, art, design, and daily interactions, offering an approach that underscores intuition and structure in understanding the surrounding environment.